Judge's Consideration in Polygamy License for The Reason of Siri Marriage (Study of Decisions in Case Number 1309/Pdt.G/2020/PA.Sal, Case Number 309/Pdt.G/2018/PA.Wno and Case Number 280/Pdt.G/2017/PA.Sgt) - Dea Shinta Rahmawati; Marisa Kurnianingsih (Universitas Muhammadiyah Surakarta, 2023)
Marriage is an interior and outer bond between a man and a woman as husband and wife with the goal of forming a happy and eternal family (household) founded on faith in the Almighty God. To enter into a polygamous marriage, the partner or applicant must meet the alternative and cumulative polygamous marriage requirements. According to Islamic law and positive law, polygamy is permissible (mubah). Polygamy continues to be a controversial issue in Indonesia. Polygamy is believed to be harmful and miserable for women, while it only benefits men. The permissibility of polygamy in Islam is not a form of inequality between men and women, considering that the conditions for polygamy are very strict. Men who wish to practice polygamy must be able to comply with the legally stipulated requirements and principles of polygamy. The judge's consideration is his opinion in making a decision, which must consider the mitigating and aggravating circumstances of the applicant. In this case, the author uses a normative legal approach as a research methodology. Descriptive qualitative research was used in this study, namely research to describe carefully, thoroughly, and population characteristics or special aspects. The data source used in this study comes from other sources and therefore is secondary. This paper attempts to identify and explain the factors considered by judges in allowing polygamy based on unregistered marriages, as well as ascertaining the legal basis and factors used by judges to allow polygamy.